Security management model for IoT devices based on international standards - Marceles Villalba, Katerine; Collazos Sandoval, Edwin Javier; Amador Donado, Siler (Ingeniería Solidaria, 2025)
Introduction:  The research was conducted with the support of the Universidad del Cauca, the Institución Universitaria Colegio Mayor del Cauca, and the Universidad de Antioquia during the year 2023.Problem: The rapid increase in IoT devices has created a gap in terms of security, as many devices lack adequate protection mechanisms, exposing them to critical vulnerabilities such as weak authentication, unencrypted data transmission, and lack of update management.Objective: To design a security management model for IoT devices based on international standards that mitigates risks associated with specific vulnerabilities and provides clear guidelines for implementing effective protection measures.Methodology: The methodology included a systematic literature review, classification of standards, and development of the model at three levels: device security, network security, and security management.Results: The results highlight the importance of encryption, network segmentation, and regulatory compliance to strengthen security in IoT environmentsConclusion: The developed security management model significantly improves the protection of IoT devices, providing an effective structure based on international standards. Additionally, future developments are proposed, such as integrating artificial intelligence and enhancing user awareness campaigns.Originality: The model's approach integrates international standards with specific practical measures to address critical IoT vulnerabilities, standing out as an advancement in the field of IoT cybersecurity.Limitations: The model was tested in a controlled environment and may require adjustments for broader or specific contexts. Additionally, practical implementation may depend on technical and human resources that not all organizations possess.
Keywords: Authentication Device; International Standards; IoT Security; Security Management; Threat Detection